an Interpretive Review of Interfaith Marriages and Validity in Indonesia Election - Muhammad Hafis; Jumni Nelli (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
The issue of interfaith marriage in Indonesia remains a hot issue to be studied from various aspects, and not infrequently we still get interpretations of verses from the Quran and regulations that say, that interfaith marriage is legally permissible and valid, in this case, katakana only, for example, the opinion of Ahmad Nurcholis who is a counselor for interfaith marriage in Indonesia. So, in this journal article, the author will examine the verses of the Quran and the rules that are the basis for the law used whether marriages between different religions are used and how valid they are in Indonesia, then how strong the arguments that allow it is. This journal research is qualitative research using juridical and philosophical approaches, where the author examines the meaning and wisdom contained in the verse and examines the regulations related to interfaith marriage. The results of this study show that interfaith marriage cannot be justified either by using paragraphs or laws and regulations in Indonesia.